Evaluating the link between periodontitis and oral squamous cell carcinoma through Wnt/β-catenin pathway: a critical review - Reyes, Montserrat; Urra, Hery; Peña-Oyarzún, Daniel (Frontiers in Oral Health, 2025)
Oral Squamous Cell Carcinoma (OSCC), the main form of oral cancer, is a major health problem globally that affects 400,000 people every year. It has been postulated that periodontitis, a chronic inflammatory disease characterized by alveolar bone resorption, is an independent risk factor for OSCC. However, the mechanisms underlying this link are not fully elucidated. It has been demonstrated that the Wnt/β-catenin pathway is key to the transformation of oral potentially malignant disorders (OPMD) towards OSCC (i.e., leukoplakia), particularly in OPMD histologically diagnosed as oral dysplasia. Using a GEO database of oral carcinogenesis (GSE85195), the transcriptional modification of 19 Wnt ligands and 4 key regulatory proteins of β-catenin, including E-cadherin, APC, AXIN and GSK3B, during leukoplakia, and early and late stages OSCC, was determined. The transcriptional expression of these targets was also assessed in periodontitis (GEO database GSE223924). Together, it was found that Wnt ligands Wnt3, Wnt3a, Wnt5b and Wnt7b are concomitantly upregulated in periodontitis and oral carcinogenesis. With these results, and the information retrieved from the literature, this review discusses the potential role of the Wnt/β-catenin pathway as a molecular mechanism that could interlink periodontitis and OSCC.